Mutational analysis of vaccinia virus nucleoside triphosphate phosphohydrolase II, a DExH box RNA helicase. - Gross, C H (1995)
Vaccinia virus nucleoside triphosphate phosphohydrolase II (NPH-II), a 3'-to-5' RNA helicase, displays sequence similarity to members of the DExH family of nucleic acid-dependent nucleoside triphosphatases (NTPases). The contributions of the conserved GxGKT and DExH motifs to enzyme activity were assessed by alanine scanning mutagenesis. Histidine-tagged versions of NPH-II were expressed in vaccinia virus-infected BSC40 cells and purified by nickel affinity and conventional fractionation steps. Wild-type His-NPH-II was indistinguishable from native NPH-II with respect to RNA helicase, RNA binding, and nucleic acid-stimulated NTPase activities. The K-191-->A (K191A), D296A, and E297A mutant proteins bound RNA as well as wild-type His-NPH-II did, but they were severely defective in NTPase and helicase functions. The H299A mutant was active in RNA binding and NTP hydrolysis but was defective in duplex unwinding. Whereas the NTPase of wild-type NPH-II was stimulated > 10-fold by polynucleotide cofactors, the NTPase of the H299A mutant was nucleic acid independent. Because the specific NTPase activity of the H299A mutant in the absence of nucleic acid was near that of wild-type enzyme in the presence of DNA or RNA and because the Km for ATP was unaltered by the H299A substitution, we regard this mutation as a "gain-of-function" mutation and suggest that the histidine residue in the DExH box is required to couple the NTPase and helicase activities.